Policy With an Asterisk: Understanding How Staff in Alternative School Settings Negotiate a Mandatory Attendance Policy to Meet the Needs of Their Students - Birioukov-Brant, Anton; Brant-Birioukov, Kiera (Frontiers in Education, 2019)
Compulsory school attendance is enacted legislation in every Canadian province. Provincial Ministry of Education attendance expectations trickle down to the school boards, which often enact punitive attendance policies. While regular attendance is important, a body of literature has highlighted the almost insurmountable obstacles many youths experience in their ability to consistently attend school. Issues such as abuse, poverty, violence and mental health disorders effectively bar a subsect of adolescents from attending school. However, attendance policies do not pay credence to these issues. Rather, school administrators are expected to follow the policies in their rigid conception. In this study, in a large city in Ontario, the school board has an attendance policy stipulating that a student over the age of 18 would be demitted from enrollment if they missed 12 consecutive days without a “legitimate” excuse. This research investigates how staff in high-needs alternative schools navigate the ethical attendance paradox: how to follow the board attendance policy, whilst simultaneously delivering an equitable education to their students. Educators are regularly faced with subjective, moral dilemmas; however, their roles become particularly challenging when they are expected to both uphold unilaterally imposed policies, and yet enact these policies in such a way that does not compromise their students’ education. This research sought to understand the professional and ethical tensions alternative high school staff experience when navigating the enforcement of mandatory attendance polices. Sixteen staff members in four alternative high schools in Ontario, Canada were sampled for this qualitative research. Through semi-structured interviews the school personnel shared the inherent difficulties of meeting the needs of their students by allowing them to miss some school, whilst meeting the legal obligations of the mandatory attendance policy established by the school board. We argue that these alternative school educators are active policy makers in their own right, as they interpret, co-opt, appropriate, and negotiate the attendance policies with the realities of these alternative school youth.